Material Deprivation and Consumption - Kus, B; Nolan, B; Whelan, C (Oxford University Press, 2017)
This article examines material deprivation and consumption in relation to poverty. In a developing country context, manifest material deprivation and inadequate levels of consumption have always been central to the conceptualization of poverty and living standards. Direct measures of failure to meet “basic needs” are widely used alongside income-based measures such as the World Bank’s “dollar a day” standard. In contrast, both research and official poverty monitoring in rich countries tend to rely on household income. This article begins with a review of recent research on material deprivation, seen primarily as a means to go “beyond income” in capturing poverty and exclusion. It then considers the mismatch between low income and measured deprivation, along with the notion of multidimensionality and the measurement issues raised in the implementation of multidimensional approaches. Finally, it analyzes conceptual and empirical issues relating to the contrast between income and consumption.